1998
DOI: 10.1176/ajp.155.5.646
|View full text |Cite
|
Sign up to set email alerts
|

12-Month Outcome of Patients With Bipolar Disorder Following Hospitalization for a Manic or Mixed Episode

Abstract: A minority of patients with bipolar disorder achieved a favorable outcome in the year following hospitalization for a manic or mixed episode. Shorter duration of illness, higher social class, and treatment compliance were associated with higher rates of recovery and more rapid recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
213
3
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 416 publications
(243 citation statements)
references
References 47 publications
19
213
3
8
Order By: Relevance
“…Twenty-eight percent did not suffer relapse though it is not clear what percent of those not taking medication were relapse free. In a 1 year follow-up of hospitalized manies with high rates of comorbid substance/alcohol abuse at admission, Keck et al (1998) report that 52% continued to abuse alcohol and/or drugs and 26% discontinued medication after discharge; in this sample, there was a 48% syndromic, 26% symptomatic, and 24% functional recovery. Goldberg et al (1995) described patients hospitalized for acute mania and found 20% not taking medication at 2 year followup.…”
Section: Discussionmentioning
confidence: 84%
“…Twenty-eight percent did not suffer relapse though it is not clear what percent of those not taking medication were relapse free. In a 1 year follow-up of hospitalized manies with high rates of comorbid substance/alcohol abuse at admission, Keck et al (1998) report that 52% continued to abuse alcohol and/or drugs and 26% discontinued medication after discharge; in this sample, there was a 48% syndromic, 26% symptomatic, and 24% functional recovery. Goldberg et al (1995) described patients hospitalized for acute mania and found 20% not taking medication at 2 year followup.…”
Section: Discussionmentioning
confidence: 84%
“…Demographic variables, such as older age [120], male sex [121, 122] and low socio-economic status [17, 18, 123], may also be considered as variables that influence the functioning of bipolar patients, although these results have yet to be sufficiently replicated. Other aspects could be environmental factors, such as social support [9, 31, 32] or life events [33].…”
Section: Resultsmentioning
confidence: 99%
“…However, a substantial proportion of bipolar patients show persistent subsyndromal symptoms, and most individuals with bipolar disorder are symptomatic more than half of their lives despite receiving pharmacological treatment [3, 4]. Even those patients who achieve full clinical remission show difficulties in making a complete functional recovery, returning to their premorbid level of functioning [5,6,7,8,9,10,11,12,13,14,15,16,17,18]. Nevertheless, psychosocial outcomes in patients with bipolar disorder have generally received less attention than those in patients with psychosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of course we know that these also are all potential terminal illnesses, given suicide rates between 10% and 19% [5,6]. And lest we believe that bipolar disorder has a "good" prognosis, recall that Keck and colleagues found that one year after hospitalization for a manic or mixed episode, only 24% of patients with bipolar type I achieved functional recovery [7]. Facts and figures such as these are absolutely necessary when talking with people in political office.…”
Section: Point: Open Access Is Important In Fact Vitalmentioning
confidence: 99%